2011
DOI: 10.1111/j.1467-8489.2011.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the Environmental Management Charge in the Cairns management area of the Great Barrier Reef Marine Park*

Abstract: Using data from a survey of more than 1000 domestic visitors to the Northern section of the Great Barrier Reef (GBR) -predominantly those travelling on live-aboard dive boats -this research investigates the (tax) efficiency of the Environmental Management Charge (EMC). The travel cost method (with a zero truncated negative binomial specification) is used to estimate the price elasticity of demand, and those estimates are used to estimate the deadweight losses, the losses in visitor numbers that could be 'blame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Other recent socio-economic work has focused on a range of issues related to tourism and the GBR (Coghlan, in press;Farr et al, 2011;Gregg and Greiner, 2008;Kragt et al, 2009;Pabel and Coghlan, 2011).…”
Section: Social and Economic Research For Improved Management Of The mentioning
confidence: 98%
“…Other recent socio-economic work has focused on a range of issues related to tourism and the GBR (Coghlan, in press;Farr et al, 2011;Gregg and Greiner, 2008;Kragt et al, 2009;Pabel and Coghlan, 2011).…”
Section: Social and Economic Research For Improved Management Of The mentioning
confidence: 98%
“…Fees (e.g., for use of MPAs) and taxes (e.g., for tourism accommodation) can generate revenue from the general public and from users of ecosystem services (the investors) that flows towards governments, communities, or non-profit organisations (the investees) to manage the MPAs or marine areas, potentially in an economically efficient and equitable manner (Knapman and Stoeckl, 1995;Farr et al, 2011). Entrance and user fees for MPAs are common globally, including notable examples in Palau, Hawaii, and Australia (Mak, 1995(Mak, , 1998Uyarra et al, 2010;GBRMPA, 2014) and have been shown to be supported by visitors in some regions .…”
Section: Finance Mechanismsmentioning
confidence: 99%
“…This study used perceived travel costs as reported by respondents. The current literature shows a slight preference for the use of reported costs (Herath and Kennedy, 2004; Prayaga et al , 2010; Farr et al , 2011). Arguably, this is because reported costs are most likely to represent the opportunity costs that respondents considered when making their trip decision (Bennett, 1996; Prayaga et al , 2010; Mwebaze and Bennett, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For single-site visitors, all the travel costs can be allocated to the site; however, for multiple-site visitors, travel costs need to be apportioned in some way between sites. There are no fixed rules on how to do this and several different approaches have been suggested (Parsons and Wilson, 1997;Loomis et al, 2000;Stoeckl and Mules, 2006;du Preez and Hosking, 2011;Farr et al, 2011;Mwebaze and Bennett, 2012). A number of studies suggest the use of dummy variables to account for multiple-site visitors so that the model, in essence, determines the proportion of total travel costs to be allocated to a given site (Parsons and Wilson, 1997;Loomis et al, 2000;Stoeckl and Mules, 2006;Mwebaze and Bennett, 2012).…”
Section: The Individual Travel Cost Methodsmentioning
confidence: 99%
See 1 more Smart Citation